The Role Of Auditory And Educational Material In Teaching English To Visually Impaired Students - Soumia, Tamma; Mohammed, Naoua (جامعة الوادي - University of Eloued, 2021)
This paper attempts to highlight the role that the auditory and tactile educational material play in teaching English to students with visual impairment (SVI). Unlike their colleagues who can use visual, auditory, and kinesthetic styles in their knowledge processing, visually impaired learners rely mostly on auditory reception without excluding the tactile, or kinesthetic modes to compensate for this limitation. In this context, both teaching methods and technology can help satisfy the special needs of these learners. On the one hand, the Audio-Lingual Method (ALM) with its oral/aural techniques can coincide with their auditory processing of learning. On the other hand, this can be reinforced with the use of technology resources such as the 3 D models, which help them in their tactile language learning. Now, this review aims to raise teachers’ awareness to develop the auditory competence of SVI so that they can improve their language learning. Therefore, this paper recommends teachers to incorporate the methods and material, which satisfy their learners with special learning needs.
Article
Keywords: Audio-Lingual Method (ALM); auditory channel; learning styles; tactile; visually impaired